Effects of a multi‐component alcohol prevention intervention at sporting events: a quasi‐experimental control group study. (23rd March 2021) - Elgán, Tobias H.; Durbeej, Natalie; Holder, Harold D.; Gripenberg, Johanna
Abstract: Background and aims: Alcohol intoxication among spectators and related problems are common at sporting events. This study estimated the impact a multi‐component community‐based alcohol prevention intervention, implemented at Swedish Premier Football (soccer) League matches, had on intoxication levels among spectators and refusal rates of alcohol service to, and arena entry of, obviously intoxicated spectators. Design: A quasi‐experimental controlled study using a repeated cross‐sectional design. Setting and participants: Spectators and sport arenas in Stockholm and Gothenburg, Sweden. Intervention and comparator: The intervention was implemented in Stockholm and consisted of community mobilisation and collaboration, training of staff and improved enforcement and policy work. Gothenburg was the comparison area and received usual care. Measurements: Primary outcomes were spectators' mean breath alcohol concentration (BrAC), proportion of spectators with high intoxication levels, (defined as BrAC ≥0.1%), overserving at licensed premises inside arenas and refused arena entry of obviously intoxicated spectators. Baseline data were collected during 2015 and follow‐up during 2016 and 2017. Findings: BrAC assessments ( n  = 10 188), arena entry attempts ( n  = 201) and alcohol purchase attempts at premises inside arenas ( n  = 495) were collected. There was evidence that the refusal rates of alcohol purchase at premises inside arenas improved differently between study areas and over time (adjusted odds ratio [aOR] = 0.28, 95% CI = 0.07, 1.06, P  = 0.060, Bayes factor [BF] = 8.60). In both study areas, the arena entry refusal rates improved over time (aOR = 5.87, 95% CI = 1.16, 29.83, P  = 0.033, BF = 17.7), but evidence that the rates improved differently between study areas and over time was equivocal (aOR = 0.57, 95% CI = 0.09, 3.56, P  = 0.543, BF = 1.2). Mean BrAC levels decreased over time in both study areas (β = −0.032, 95% CI = −0.050, −0.015, P  < 0.001), and differently (β = 0.104, 95% CI = 0.061, 0.146, P  < 0.001), but evidence for an interaction effect was equivocal (β = −0.002, 95% CI = −0.022, 0.018, P  = 0.868, BF = 1.0). Evidence was equivocal regarding whether the proportion of spectators with high intoxication levels decreased differently between study areas and over time (aOR = 1.17, 95% CI = 0.91, 1.50, P  = 0.220, BF = 2.2). Conclusions: A multi‐component community‐based alcohol prevention intervention at sporting events may have increased staff intervention toward obviously intoxicated spectators. It was not clear whether this translated into a reduction in intoxication, which can be explained by improvements in the comparison area.